Press and pliant governors - Padhy, Krushna Singh, 1949- (New Delhi : Kanishka Publishers, Distributors, 1996)
Indepth analysis of the appointment and dismissal of the Governors, gross misuse of their offices, and abuse of Article 356 of the Constitution in general and dissolution of the Karnataka Assembly in particular.
Includes bibliographical references (p. [209]-221) and index.
Keywords: Governors -- India -- Karnataka -- Powers and duties; Executive power -- India; Press and politics -- India -- Karnataka; India -- Politics and government -- 20th century